2004
DOI: 10.1007/s11096-004-2849-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care, European developments in concepts, implementation, teaching, and research: a review

Abstract: This article discusses the concept of pharmaceutical care especially from the European perspective. It tries to clarify the current status of pharmaceutical care research and implementation, and if and how it can be part of the practice of pharmacy. Pharmaceutical care basically means improving the medication use process in order to improve outcomes, including the patients' quality of life, and that involves a focus change for pharmacy from product to patient. This change in focus also implies that the pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 63 publications
1
41
0
4
Order By: Relevance
“…Research has identified barriers and facilitators for the implementation process in order to promote the uptake of services [3,[10][11][12][13]. Some argued that the solutions to service implementation were in ensuring the clinical expertise of pharmacists and remuneration for service provision [14,15]. However, their impact evidenced in the Australian context has not been as expected [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified barriers and facilitators for the implementation process in order to promote the uptake of services [3,[10][11][12][13]. Some argued that the solutions to service implementation were in ensuring the clinical expertise of pharmacists and remuneration for service provision [14,15]. However, their impact evidenced in the Australian context has not been as expected [5].…”
Section: Introductionmentioning
confidence: 99%
“…As an example let us consider a pharmacy, where the role of competence management is increasing all the time as they are moving away from their original role on drug supply towards a more inclusive focus on pharmaceutical care [6,7,8]. This new trend sets significant challenges on pharmacists' skills as healthcare is a field where the fast development of drug treatment and the introduction of new drugs require specialized skills and knowledge that need to be renewed frequently [9,10,11].…”
Section: Troductiomentioning
confidence: 99%
“…In recent years there has been a trend in pharmacy practice to move away from its original role on drug supply towards a more inclusive focus on patient care [1,2,3]. This trend in pharmacy practice is called pharmaceutical care [4,5,6].…”
Section: Introductionmentioning
confidence: 99%